A "Silent Revolution": school reforms and Italy's educational gender gap in the Liberal Age (1861-1921) - Gabriele Cappelli; Michelangelo Vesta (European Historical Economics Society (EHES), 2020)
This paper explores the evolution of the human capital gender gap in Liberal Italy (1871 – 1921). First, we show that Italy lagged some 50 years behind more advanced countries like France, Prussia and the UK, and that the regional divide in gendered literacy was unparalleled in the rest of Europe. Next, we test whether the shift to primary-school centralization in 1911 (the Daneo-Credaro Reform) brought about a decisive improvement in female literacy. We rely on a brand-new, cross-section micro (municipal) dataset of literacy rates in 1911 and 1921, as well as their potential determinants around 1911. Such data, combined with Propensity Score Matching to improve identification, shows that primary-school centralization increased the average annual growth of female literacy by 0.78 percentage points. Thus, even though the Reform did not aim at girls specifically, it brought about the unintended consequences of more rapid human capital accumulation for women and – ceteris paribus – a reduced educational gender gap. We briefly discuss why this "Silent Revolution" likely had important implications for Italy's economic history.
Keywords: I25; J16; N3; 330; Gender; primary schooling; Liberal Age; Italy